Analysis of Metacognitive Characteristics in Japanese University Students of Teacher Education Using the Metacognitive Awareness Inventory - Satoshi Kusaka; Shino Manabe (Indonesian Educational Research Journal, 2025)
The aim of this research was to shed light on the metacognitive profiles of students attending a teacher education university in Japan and to provide insights for curriculum design that enhances these skills. Data were collected in October 2023 from 146 first- and third-year students enrolled in teacher education programmes at a university, Japan, using the 52-item Metacognitive Awareness Inventory for Adults (MAI) administered online with a six-point Likert scale. The MAI is a widely used self-report instrument that captures perceived metacognitive awareness across subdomains of knowledge of cognition and regulation of cognition. Because it assesses perceptions rather than directly observed behaviour, findings should be interpreted as self-reported tendencies. Descriptive statistics and Pearson correlations were computed for MAI subdomains. Participants generally perceived themselves as possessing strong metacognitive abilities (overall mean = 3.98/6), with metacognitive knowledge slightly higher than metacognitive regulation. Procedural knowledge was strongly associated with monitoring (r = .62, p < .01) and evaluation (r = .52, p < .01), suggesting that students who report stronger strategy-use knowledge also report more frequent self-checking and post-task reflection. Monitoring correlated positively with debugging (r = .56, p < .01), whereas debugging correlated negatively with evaluation (r = −.50, p < .01), indicating a possible tension between immediate error correction and broader reflective assessment. These findings imply that teacher education curricula should pair explicit strategy instruction with structured opportunities for monitoring and post-task evaluation to strengthen balanced metacognitive regulation.